Comparison of the performance of hydraulic lime- and clay-based grouts in the repair of rammed earth - Silva, Rui André Martins (2018)
Earth constructions constitute an important part of the built heritage and are spread worldwide. Rammed earth is among the most used earth construction techniques, though it exhibits a high seismic vulnerability. Nevertheless, the structural behaviour of rammed earth structures is still insufficiently comprehended. Thus, the preservation of this built heritage requires exhaustive characterisation of its mechanical and structural behaviours, as well as the development and validation of adequate intervention solutions. In this context, this paper presents an experimental program aimed at evaluating the effectiveness of grout injection to repair cracks and at further characterising the in-plane shear behaviour of rammed earth walls. The experimental program included the testing of rammed earth wallets under diagonal compression, which were subsequently repaired with injection of a clay-based or a hydraulic lime-based grout, and retested. Furthermore, sonic tests were conducted on the wallets before the destructive tests. The obtained results allowed to highlight that both grouts led to similar repairing performances, though the interlocking contribution promoted by the coarse particles of the rammed earth to the shear behaviour was found to be irrecoverable.